Shariah-Based Carbon Credit Transactions: A Regulatory Analysis Within Islamic Economic Law In Indonesia - Arianti Wulan; Amir Tajrid (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose  – The carbon market's development for net-zero emissions needs a regulatory framework that guarantees environmental integrity, legal certainty, and market accountability. Indonesia established in carbon market governance with the Economic Value of Carbon (NEK) policy and operates carbon trading through IDXCarbon. Currently, there are no regulations governing Sharia-based carbon credit transactions. This gap is increasingly relevant due to the growth of Sharia economic practices, including trading carbon units from waqf forests managed by the Indonesian Waqf Board (BWI), the Digital Carbon Tracking service from Bank Syariah Indonesia (BSI), and opportunities for Sharia financial institutions in carbon trading. Method –  This study employs a normative-doctrinal legal approach, utilizing regulatory mapping, regulatory gap analysis, and Sharia compliance assessment to examine carbon market regulations and the principles of Sharia economic law. Result – Research shows that carbon market regulations in Indonesia have established technical and institutional governance frameworks but have not yet accommodated the needs of Sharia-compliant transactions. Regulatory gaps include the legal status of carbon units as objects of contracts, Sharia screening, Sharia governance, the integrity of Measurement, Reporting, and Verification (MRV), information disclosure, and institutional coordination, which could potentially lead to legal uncertainty and Sharia compliance risks. Implication – This study proposes Minimum Regulatory Standards (MRS) along with an institutional implementation roadmap as a regulatory blueprint through coordination among the Ministry of Environment and Forestry (KLHK), the Financial Services Authority (OJK), the Sharia Council of Indonesia (DSN-MUI), the Indonesian Sharia Board (BWI), and IDXCarbon to establish an integrated Sharia regulatory layer within the national carbon market governance framework.